Selamatan Bersih Desa sebagai Wujud Ucapan Syukur dalam Kontradiksi Budaya Jawa: Jaman Dahulu dan Sekarang - Sita Nuraseh (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
In ancient times, the majority of Javanese people still carried out the culture or tradition of salvation. This research uses the tradition or clean culture of the village or also known as merti desa as the object of research. Village cleaning is an activity that is a symbol of public gratitude to God Almighty for all His gifts. This gift can be in the form of anything such as sustenance, safety, harmony and peace. However, along with the development of the era and cultural acculturation, there have been cultural changes in the present era, including changes in the culture of clean village salvation. Cultural changes in society are usually caused by the community itself, or come from immigrant communities. The purpose of this research is to provide information about Javanese society, Javanese culture, and the tradition of village clean salvation. This study used descriptive qualitative method. The results of this study indicate that there have been several changes in the implementation of the village clean salvation tradition. The implementation in ancient times is more complete when compared to the implementation today.